2019
DOI: 10.1096/fba.1018
|View full text |Cite
|
Sign up to set email alerts
|

S -Nitrosated alpha-1-acid glycoprotein exhibits antibacterial activity against multidrug-resistant bacteria strains and synergistically enhances the effect of antibiotics

Abstract: Alpha‐1‐acid glycoprotein (AGP) is a major acute‐phase protein. Biosynthesis of AGP increases markedly during inflammation and infection, similar to nitric oxide (NO) biosynthesis. AGP variant A (AGP) contains a reduced cysteine (Cys149). Previously, we reported that S‐nitrosated AGP (SNO‐AGP) synthesized by reaction with a NO donor, possessed very strong broad‐spectrum antimicrobial activity (IC50 = 10−9‐10−6 M). In this study, using a cecal ligation and puncture animal model, we confirmed that AGP can be end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Lipocalins are involved in multiple other functions, such as olfaction, gustation and prostaglandin D 2 synthesis ( 19 , 39 , 56 ). Several lipocalin proteins are acute-phase proteins, thus related to inflammation and innate immunity ( 58 , 59 ). Therefore, neutrophil gelatinase-associated lipocalin or alpha-1-acid glycoprotein, for example, may be used as inflammatory biomarkers in medical conditions ( 60 , 61 ).…”
Section: Lipocalinsmentioning
confidence: 99%
“…Lipocalins are involved in multiple other functions, such as olfaction, gustation and prostaglandin D 2 synthesis ( 19 , 39 , 56 ). Several lipocalin proteins are acute-phase proteins, thus related to inflammation and innate immunity ( 58 , 59 ). Therefore, neutrophil gelatinase-associated lipocalin or alpha-1-acid glycoprotein, for example, may be used as inflammatory biomarkers in medical conditions ( 60 , 61 ).…”
Section: Lipocalinsmentioning
confidence: 99%
“…Also, pyocyanin, elastase, and proteases are the main virulence factors of P. aeruginosa , which is enhance the pathogenesis of bacteria 14 . Several studies indicated that the essential role of virulence factors in the pathogenesis of P. aeruginosa in animal models 15 . To date, the researchers are studying the design of novel antibacterial agents that suppressed antibiotic resistance and virulence factors 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicated that the essential role of virulence factors in the pathogenesis of P. aeruginosa in animal models 15 . To date, the researchers are studying the design of novel antibacterial agents that suppressed antibiotic resistance and virulence factors 15,16 . Hence, the design of safe and effective new antimicrobial agents with a wide range of effects is necessary to prevent and treat infections caused by P. aeruginosa 17 .…”
Section: Introductionmentioning
confidence: 99%